2016
DOI: 10.1097/md.0000000000002699
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Diabetes and Smoking Status to Hepatocellular Carcinoma Mortality

Abstract: The relationship of diabetes and smoking status to hepatocellular carcinoma (HCC) mortality is not clear. We aimed to investigate the association of smoking cessation relative to diabetes status with subsequent deaths from HCC.We followed up 51,164 participants (aged 44–94 years) without chronic hepatitis B or C from 1 January 1998 to 31 December 2008 enrolled from nationwide health screening units in a prospective cohort study. The primary outcomes were deaths from HCC.During the study period, there were 253 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…We were able to find 10 studies in the English literature that analyzed the correlation of smoking and HCC mortality[ 33 - 42 ]. Large cohort studies indicating an impact of smoking habit on HCC mortality have been reported form Japan[ 33 , 34 ], the United Kingdom[ 35 ], China[ 36 ] and Taiwan[ 37 - 39 ]. In contrast, several studies reported a negative correlation between HCC mortality and smoking habit, although those studies analyzed relatively small numbers of HCC cases (262-552 cases)[ 40 - 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We were able to find 10 studies in the English literature that analyzed the correlation of smoking and HCC mortality[ 33 - 42 ]. Large cohort studies indicating an impact of smoking habit on HCC mortality have been reported form Japan[ 33 , 34 ], the United Kingdom[ 35 ], China[ 36 ] and Taiwan[ 37 - 39 ]. In contrast, several studies reported a negative correlation between HCC mortality and smoking habit, although those studies analyzed relatively small numbers of HCC cases (262-552 cases)[ 40 - 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several models, diabetes is one of the variables [10, 11]. It is also reported that history of diabetes is associated with deaths from HCC [13]. Patients with DM showed significantly lower overall survival than those without DM [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…The examined predictor variables were restricted to lifestyle factors that have been previously associated with HCC (5)(6)(7)(26)(27)(28)(29)(30)(31)(32)(33) and that were used in the preexisting HLI (18,19). These included BMI (continuous, kg/m 2 ), average lifetime alcohol intake (continuous, g/day), the diet score (continuous), physical activity (continuous, metabolic equivalent of task MET-h/week), smoking (never, ex-smokers quit > 10 years, ex-smokers quit 10 y, current smokers 15 cig/day, current smokers > 15 cig/ day).…”
Section: The Lifestyle Variablesmentioning
confidence: 99%
“…HCC is a multifactorial disease strongly associated with lifestyle factors, most of which are modifiable (5). While hepatitis infection, including both HBV and HCV, remains its primary risk factor, other exposures, such as obesity, alcohol drinking, diabetes, smoking, physical activity, and some dietary items, have also been related to HCC risk (6)(7)(8). Understanding the underlying etiology of HCC is key to help develop disease prevention strategies, including through the identification of metabolic signatures.…”
Section: Introductionmentioning
confidence: 99%